THE ROLE OF COMMUNICATION WITHIN ORGANIZATIONAL ENVIRONMENT - Corrêa, Vagner Marcondes; Soares, Nathalia Maria (Revista Interface Tecnológica, 2020)
This work aims to show the importance of communication within the company and the need to plan competitive strategies in this field, with new information technologies. Valuing the quality and efficiency in the processes directly reflect on the provision of services and products, being a key point in all sectors of the company, from inputs, through the process of transformation, distribution, even after-sales, demonstrating the benefits of communication within the company. The project is based on bibliographic research in books, websites, monographs and scientific articles, together with strategies and tools, creating relationships with customers, achieving the company’s objectives. Qualitative and subjective results collaborate to understand the role of business communication and some of its competitive strategies. Communication when used effectively contributes to the team’s motivation, improving results, productivity and thus, all this knowledge of the process makes employees feel confident and encouraged.